NCOG-51. CORRELATION BETWEEN TUMOR VOLUME AND SERUM PROLACTIN AND IMPACT OF TUMOR CELLULAR DENSITY ON PROLACTINOMA SURGICAL OUTCOMES IN A COHORT OF 181 PATIENTS. (9th November 2020) - Pereira, Matheus; Oh, Taemin; Joshi, Rushikesh; Haddad, Alexander; Pereira, Kaitlyn; Osorio, Robert; Donohue, Kevin; Peeran, Zain; Sudhir, Sweta; Jain, Saket; Beniwal, Angad; Gurrola, José; et al.
Abstract: INTRODUCTION: Prolactinomas are common pituitary adenomas managed medically or surgically. METHODS: Reviewed 181 prolactinomas resected transsphenoidally 2012-2019. Tumor volumes were quantified using BrainLab Smartbrush. Pearson correlation analysis and linear regression were used to identify associations between tumor volumes and serum prolactin. Tumor density was defined as serum prolactin divided by tumor volume. RESULTS: Mean tumor volume was 6.33cm 3 and mean pre-op prolactin was 803.4ug/L, with men having larger (12.11 vs 2.93cm 3 ;p< 0.001) and women having denser (173.9 vs 107.6ug/L/cm 3 ;p=0.011) prolactinomas. Pearson correlation (R=0.688;p< 0.001) and linear regression revealed a strong association between pre-op volume and prolactin levels, with 96.9g/L increase in prolactin/cm 3 increase in volume (p< 0.001); this holds true for men (R=0.584;p< 0.001) and women (R=0.939;p< 0.001), with women demonstrating greater prolactin/cm 3 tumor density (186.5 vs 75.0ug/L;p< 0.001). MiB index did not correlate with pre-op volume (p=0.449) or pre-op prolactin (p=0.452). Logistic regression showed decreased biochemical remission with increasing pre-op volume (OR=0.891;p< 0.001). Increased MiB index (p=0.971) and p53 (p=0.525) staining did not affect remission rates. Positive PIT-1 staining was associated with higher remission rates (OR=2.508;p=0.005). Patients without remission had denser tumors (149.9 vs. 100.6ug/L/cm 3 ;p=0.013), with Pearson correlation yielding R=0.736 between pre-op volume and pre-op prolactin (p< 0.001), and R=0.476 between residual volume and post-op prolactin (p< 0.001). Patients without remission exhibited 142.9ug/L increase in prolactin/cm 3 of pre-op volume (p< 0.001), higher than the 58.9ug/L increase in prolactin/cm 3 in patients with remission (p< 0.001). Patients without remission had residual tumors with 68.4ug/L increase in prolactin/cm 3 of remaining volume after resection (p< 0.001). CONCLUSION: Our analysis revealed significant correlation between prolactinoma volume and serum prolactin levels. Patients without remission had greater tumor cellular density than those with remission. The volume-prolactin correlation persisted post-operatively, although surgery reduced tumor density. These results could identify prolactinomas for which surgery could achieve biochemical remission.